Analysis and Prevention of Industrial Injury in the Construction Sector - Pahomov, Roman; Zyma, Oleksandr; Dyachenko, Evgen (International Journal of Engineering and Technology, 2018)
Industrial accidents with fatal consequences in Ukraine were investigated in the paper. International experience of injury prevention was briefly analyzed in the article. The dynamics of Industrial accidents with fatal consequences in Ukraine from 1992 to 2016 was considered. The main reasons that significantly affected the level of injury in the construction industry and in the building materials industry from 2013 to 2016 were identified and analyzed. Methods of analysis of accidents and occupational diseases at the workplace were considered. The forecast of accidents with fatal consequences for three years from 2017 to 2019, with the usage of an one-factor forecast model on the basis of a trend logarithmic curve was developed. Recommendations for the prevention and reduction of the level of injury at the enterprises of the construction industry were developed.Â Â